The Physical Properties and Self‐Assembly Potential of the RFFFR Peptide. (30th September 2016) - Slyngborg, Morten; Nielsen, Dennis Achton; Fojan, Peter
Abstract: The self‐assembly of fibers from peptides has attracted a tremendous amount of attention due to its many applications, such as in drug‐delivery systems, in tissue engineering, and in electronic devices. Recently, the self‐assembly potential of the designer peptide RFFFR has been reported. Here it is experimentally verified that the peptide forms fibers that are entangled and form solid spheres without water inside. Upon dilution below the critical fiber concentration, the fibers untangle and become totally separated prior to dissolution. These structures readily bind thioflavin T, resulting in a characteristic change in fluorescent properties consistent with β‐sheet‐rich amyloid structures with aromatic/hydrophobic grooves. The circular dichroism spectroscopy data are dominated by a π→π* transition, thus indicating that the fibers are stabilized by π‐stacking. Contrary to what was expected, the dissolution of the spheres/fibers results in increasing fluorescence anisotropy over time. This is explained in terms of HomoFRET between phenylalanine residues with a T‐shaped π‐stacking mode, which was determined in another study to be the dominant mode through atomistic simulations and semiempirical calculations. Kelvin probe force microscopy measurements indicate that the spheres and fibers have a conductivity comparable to that of gold. Hence, these self‐assembled structures might be applicable in organic solid‐state electronic devices. The dissolution properties of the spheres further suggest that they might be used as drug‐delivery systems. Abstract : Supramolecular peptide structures : The RFFFR peptide self‐assembles into fibers that entangle into sphere‐like structures. These spheres untangle below a critical concentration and so might be applicable as a drug‐delivery system. Furthermore, the spheres conduct electricity, and the fibers might also find applications in molecular electronics.